Cultural Conservation of Wong Kejawen Religion (Folklore Study of the Kejawen Community in Sidorejo Village, Batang Regency) - Martanti, Nadia Luki; Mukti, Handika (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2023)
The Kejawen tradition in Sidorejo is one of the cultural icons in Batang Regency. The Balekambang site is one proof of the existence of Javanese culture in Sidorejo. Various traditions are also passed down by the Kejawen people to future generations for their culture. This research was made to examine the cultural conservation carried out by the Kejawen people in Sidorejo through folklore studies. The research method used is qualitative with an ethnographic study approach. Data triangulation was used with data collection techniques in the form of observation, interviews, and documentation studies. The results showed that the Javanese people still follow the ancestral tradition. Balekambang site and the tradition of bathing by burning offerings as a form of cultural conservation carried out by the brand. Meanwhile, the surrounding community in Sidorejo Village does not question the existence of a tradition that is preserved by the kejawen people so that it shows an attitude of tolerance, concern, and can preserve the conservation value of the kejawen people.